Preferensi Masyarakat terhadap Produk Wadi’ah pada Bank BTN Syariah Parepare - Agung Kurniawan; Suarning; M. Ali Rusdi (BANCO: Jurnal Manajemen dan Perbankan Syariah, 2021)
This study will examine two problems, namely: How do the products Wadi‟ah at Bank BTN sharia Parepare and What are Community Preferences on Wadi‟ah products at Bank BTN Syariah Parepare. The purpose of this research to find out what people's preferences are when listening and knowing regarding Wadi‟ah products at Bank BTN Syariah Parepare. This type of research is field research that is qualitative descriptive. The approach used is a phenomenological approach. The data collection technique is using the observation method, the dept interviews and documentation. Data analysis techniques using Data Reduction (Data Reduction), Data Display (Data Presentation), Conclusing Drawing/Verification (Draw a conclusion). The results of this study indicate that: 1) Wadi‟ah products at Bank BTN Syariah Parepare are a pure deposit from a party that saves or entrust to the party receiving the deposit to be used or not used in accordance with mutually agreed terms. Wadi‟ah products in Bank BTN Syariah Parepare uses a profit-sharing system, calculated based on the ratio is multiplied by the Bank's income on the funds deposited by the customer. 2) Public preference for Wadi‟ah products at Bank BTN Syariah Parepare influenced by several preference concepts, namely: Completeness, Transivity, Continuity, and More is better. People's preferences are also affected by several factors, namely: Cultural Factors, Social Factors, Personal Factors, and Psychological Factors